Sequential Sampling Models of Same-Different Data and How They Explain the Fast-Same Effect. - Goulet, Marc-André; Cousineau, Denis (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2020)
There have been many empirical endeavors to explain the fact that participants correctly identify same stimuli faster than different stimuli. Despite a large body of literature, a conclusive and unanimous consensus to explain this effect is lacking. The present study offers a new perspective on the samedifferent task using best-fitting parametric values of 2 sequential sampling models (linear ballistic accumulator [LBA] and drift-diffusion model [DDM]) to evaluate the contribution of 3 theoretical concepts (starting point, accumulation rate, and base time) to the fast-same effect. Eighteen participants were recruited to perform 3 tasks in which they compared letter strings (a) in a normal setting, the control task; (b) with lower contrast, the contrast task; and (c) based on nominal identity, the case task. Both the LBA and the DDM suggests that participants have faster base time in the same condition compared with the different condition. They also suggest that the number of letters and the number of differences influence the accumulation rate. These results suggest that the cognitive processes do not accumulate information as efficiently when the workload is increased. Finally, the limited predictive power of the best-fitting models suggests that better theoretical grounds are needed to identify fundamental cognitive concepts underlying same-different judgments.